Geophysical and geological characterisation of dredge locations from RV Southern Surveyor voyage ss2012_v06 (ECOSATI): hotspot activity in northern Zealandia. Issue 1 (1st December 2018) - Seton, Maria; Meffre, Sebastien; Williams, Simon; Micklethwaite, Steven; Mortimer, Nick; Zahirovic, Sabin
Abstract : In October-November 2012 a geophysical mapping and dredging campaign in the eastern Coral Sea was conducted on the RV Southern Surveyor during voyage ss2012_v06 (ECOSATI). Part of this campaign was focussed in northernmost Zealandia where volcanic seamounts and uplifted portions of the Lord Howe Rise were targeted to determine the age and location of the northern portion of the Lord Howe Seamount Chain. Geophysical and geological analysis of the dredge sites from the southernmost South Rennell Trough and Chesterfield Plateau confirm the extension of the Lord Howe Seamount Chain ~200 km northward than previously identified, with an age-progression extending to ~27-28 Ma. These new samples, together with previously published samples from the youngest part of the chain, show consistency with both Indo-Atlantic and Pacific hotspots. The average magma flux rate of the Lord Howe hotspot is estimated at 0.4 m 3 /s, which is similar to the rates of crustal production at the South Rennell Trough, A peak in magmatism along the trail in the late Oligocene may be related to a slowdown in the motion of the Australian plate sometime between 27-23 Ma. The results of the geophysical and geological sampling and estimates of magma flux from the Lord Howe Seamount Chain will assist in thermal history modelling in the sedimentary basins of northern Zealandia and will help provide a geological framework for frontier resource exploration in this region.